2014
DOI: 10.1371/journal.pone.0101050
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between Exposure to Magnetic Fields and Embryonic Development in the First Trimester

Abstract: ObjectiveTo explore the correlation between maternal magnetic field (MF) exposure in daily life and embryonic development.MethodsA cross-sectional study was conducted among 149 pregnant women who were seeking induced abortion of unwanted pregnancies. Participating women were asked to wear an EMDEX Lite magnetic field meter for a 24-h period to obtain MF exposure level within 4 weeks following the abortion. Embryonic bud and sac lengths were measured through B-mode ultrasound before the surgical abortion. Embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Over the years, a few observational studies in human populations have suggested a possible link between MF exposure during pregnancy and an increased risk of miscarriage 6 11 including two studies published in 2002 that increased the public awareness of such an association 12 , 13 . In addition, one study examined human embryonic tissues to assess the association between EMF exposure and embryonic growth, and observed an increased risk of impaired embryonic bud growth and apoptosis associated with exposure to higher MF level 14 , providing some direct evidence of adverse biological impact of EMF exposure on embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, a few observational studies in human populations have suggested a possible link between MF exposure during pregnancy and an increased risk of miscarriage 6 11 including two studies published in 2002 that increased the public awareness of such an association 12 , 13 . In addition, one study examined human embryonic tissues to assess the association between EMF exposure and embryonic growth, and observed an increased risk of impaired embryonic bud growth and apoptosis associated with exposure to higher MF level 14 , providing some direct evidence of adverse biological impact of EMF exposure on embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…The device collects MF measurements from triple-axis in milligauss (1mG = 0.1 μt) in the extremely low frequency band ranging from 40 to 1000 Hz, which covers the dominant MF of 50 Hz power-line frequency in China. The meter has been widely used in epidemiologic studies [5, 8, 15].…”
Section: Methodsmentioning
confidence: 99%
“…As developing embryo and fetus are much more susceptible to environmental toxins including MF, many studies have focused on the impact of prenatal MF exposure on fetal growth as well as other health outcomes of offspring, such as miscarriage, obesity, asthma, etc. [3, 4, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Su et al (2014) recently examined the potential relationship between exposure to magnetic fields and abnormal embryonic development in a cross-sectional study, postulating that miscarriage may be preceded by and perhaps causally-related to such developmental effects. In that study, 130 working and nonworking women that were seeking an elective abortion were recruited from a maternal and child health center located in Shanghai, China.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…Exposures were characterized within 4 weeks following abortions with a personal exposure monitor worn at the hip that collected data once every 4 sec for a single, 24-hr period, and, as a result, there was temporal ambiguity between exposure and outcome. Su et al (2014) selected the TWA, median, and 75 th percentile as potentially biologically-relevant metrics a priori . While embryonic sac length and apoptosis levels were not markedly related to personal magnetic field exposure measures, embryonic bud length [cases = 19 (bud length ≤25 th percentile), controls = 46 (bud length >25 th percentile)] was inversely associated with a 75 th percentile magnetic field exposure ≥0.82 mG (adjusted OR: 3.95, 95% CI: 1.1, 14.2).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%